Exploring the impact of "massclusivity" campaigns on brand love through online brand communities - Santos, Joana Fonseca dos (2018)
The current dissertation aims to understand the impact of the development of Massclusivity (massive and exclusive) campaigns or product ranges on the brand love of online brand communities. Having in mind the topic defined, this research comprises the analysis of the meaning and perception of luxury; the marketplace associated to it – with a focus on the fashion consumption segment -; and the impact of the trends such as digital luxury and Massclusivity. In order to understand the dynamics of the selected market, this investigation is based on core of relationship marketing concepts, brand love, brand communities and consumer-brand relationship. A netnography analysis was conducted concerning the interactions between the selected brands - a luxury fashion brand, Gucci, and a mass market fashion brand, H&M – and the respective online brand communities on the Social Networking Sites Facebook and Instagram, during a specific period of time defined according to the launch of Massclusivity campaigns by each of one these brands. The content gathering from this netnography methodology took place on the online brand communities defined, and it allowed the compilation of a total of 336,509 interactions. Gucci community members’ interactions were analyzed considering these brand’s publications from March 2017 to March 2018; while H&M community members’ interactions considered these brand’s posts from July 2017 to March 2018. This research provides valuable insights not only for luxury brands but also for the fashion market in general, by perceiving that despite the low impact on the brand love of OBCs, the development of massclusivity campaigns have several impacts identified: generate awareness towards the brand, increases consumers’ engagement on SNS and promotes communities’ expansion. These consequences are directly related to the curiosity that these marketing strategies generate towards the brands, which may be considered powerful to luxury brands who intend to diversify their audience and become competitive among a traditional sector.